Development of solid-state avalanche amorphous selenium for medical imaging - Scheuermann, James R. (Med Phys, 2015)
PURPOSE: Active matrix flat panel imagers (AMFPI) have limited performance in low dose applications due to the electronic noise of the thin film transistor (TFT) array. A uniform layer of avalanche amorphous selenium (a-Se) called high gain avalanche rushing photoconductor (HARP) allows for signal amplification prior to readout from the TFT array, largely eliminating the effects of the electronic noise. The authors report preliminary avalanche gain measurements from the first HARP structure developed for direct deposition onto a TFT array. METHODS: The HARP structure is fabricated on a glass substrate in the form of p-i-n, i.e., the electron blocking layer (p) followed by an intrinsic (i) a-Se layer and finally the hole blocking layer (n). All deposition procedures are scalable to large area detectors. Integrated charge is measured from pulsed optical excitation incident on the top electrode (as would in an indirect AMFPI) under continuous high voltage bias. Avalanche gain measurements were obtained from samples fabricated simultaneously at different locations in the evaporator to evaluate performance uniformity across large area. RESULTS: An avalanche gain of up to 80 was obtained, which showed field dependence consistent with previous measurements from n-i-p HARP structures established for vacuum tubes. Measurements from multiple samples demonstrate the spatial uniformity of performance using large area deposition methods. Finally, the results were highly reproducible during the time course of the entire study. CONCLUSIONS: We present promising avalanche gain measurement results from a novel HARP structure that can be deposited onto a TFT array. This is a crucial step toward the practical feasibility of AMFPI with avalanche gain, enabling quantum noise limited performance down to a single x-ray photon per pixel.